To inhabit research-creation labs notes from the experience - Romero Sánchez, Mónica Marcell (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Current arts practices have exceeded their limits to the point that a creator is considered to be a deep thinker of her/himself and of the actions that she/ he accomplishes in specific contexts. Therefore, arts practices are formed by the tradition of their disciplines and their numerous transformations, as well as by a high reflexive component around its social function of integrating the community. Based on such a premise, I will deal with some considerations about the national program of visual arts education in the informal field: the research-creation labs (implemented in 2004 under the tutelage of the Ministry of Culture – Arts Department) that have influenced the way of teaching arts in our country and their ways of passing around and articulating with the Regional and National Artists Rooms. The shared reflections are part of the research project: ‘Among institutional discourses and micronarratives. Notes for the construction of a critical look at the visual arts research-creation labs’, which is in process and has its interest focused on discussing the arts practices with respect to the pedagogical practices in the institutional framework they are part of and on demonstrating in this way their tensions.